Optimizing Implementation of Obesity Prevention Programs: A Qualitative Investigation Within a Large‐Scale Randomized Controlled Trial. Issue 1 (6th August 2015) - Kozica, Samantha L.; Teede, Helena J.; Harrison, Cheryce L.; Klein, Ruth; Lombard, Catherine B.
Abstract: Purpose: The prevalence of obesity in rural and remote areas is elevated in comparison to urban populations, highlighting the need for interventions targeting obesity prevention in these settings. Implementing evidence‐based obesity prevention programs is challenging. This study aimed to investigate factors influencing the implementation of obesity prevention programs, including adoption, program delivery, community uptake, and continuation, specifically within rural settings. Methods: Nested within a large‐scale randomized controlled trial, a qualitative exploratory approach was adopted, with purposive sampling techniques utilized, to recruit stakeholders from 41 small rural towns in Australia. In‐depth semistructured interviews were conducted with clinical health professionals, health service managers, and local government employees. Open coding was completed independently by 2 investigators and thematic analysis undertaken. Findings: In‐depth interviews revealed that obesity prevention programs were valued by the rural workforce. Program implementation is influenced by interrelated factors across: (1) contextual factors and (2) organizational capacity. Key recommendations to manage the challenges of implementing evidence‐based programs focused on reducing program delivery costs, aided by the provision of a suite of implementation and evaluation resources. Informing the scale‐up of future prevention programs, stakeholders highlighted the need to build local rural capacity through developing supportive university partnerships, generating local program ownership and promoting active feedback to all program partners. Conclusion: We demonstrate that the rural workforce places a high value on obesity prevention programs. Our results inform the future scale‐up of obesity prevention programs, providing an improved understanding of strategies to optimize implementation of evidence‐based prevention programs.